Mothers’ Perception, Utilisation, and Satisfaction with Primary Healthcare Services for Children in Ishielu LGA, Ebonyi State, Nigeria - Okeke; Kingsley Udechukwu; Clement Felix Chimereuche; Eze; Clementina Nkiru (International Journal of Modern Science and Research Technology, 2026)
Primary Health Care (PHC) is vital in enhancing children’s health status, particularly in rural areas that lack better-equipped healthcare facilities. However, the utilization, perception, and satisfaction associated with PHC services for child healthcare vary across settings. This study assessed the perception, utilisation, and satisfaction with Primary Health Care services for child healthcare among mothers in Ishielu Local Government Area, Ebonyi State, Nigeria. A community-based descriptive cross-sectional design was used. A total sample size of 397 women of reproductive age was selected through cluster sampling technique. Data were collected using structured questionnaires which were analysed descriptively in SPSS version 26. The findings showed that most respondents had a positive perception of PHC services, particularly in terms of accessibility (72.8%), short waiting time (89.7%), and effectiveness of treatment (94.5%), although affordability was a concern. Almost all respondents (98.2%) had previously used PHC services, but regular utilization was moderate, with only 13.9% always visiting. PHC centres were the most preferred locations for immunization (72.0%) and treatment of childhood illnesses (76.1%). Satisfaction with services was generally high across most areas, except for distance, where only 27.2% expressed satisfaction. In summary, PHC services for child healthcare have been well received and utilized by many people in the research location, but cost and distance remain constraints on usage. Accessibility should be increased, costs reduced, and community perception improved to increase patronage of services and improve child health outcomes.